2021
DOI: 10.1186/s40246-020-00302-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessments of germline deletion structural variants reveal the association between prognostic MUC4 and CEP72 deletions and immune response gene expression in colorectal cancer patients

Abstract: Background Functional disruptions by large germline genomic structural variants in susceptible genes are known risks for cancer. We used deletion structural variants (DSVs) generated from germline whole-genome sequencing (WGS) and DSV immune-related association tumor microenvironment (TME) to predict cancer risk and prognosis. Methods We investigated the contribution of germline DSVs to cancer susceptibility and prognosis by silicon and causal infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In the breast cancer scenario, IFNGR1 expression is abridged or wholly lost and the immunoreactivity of heterogeneous IFNGR1 is linked to the morphological heterogeneity in breast cancer cells . One of the essential biomarkers shortlisted in our study is long intergenic nonprotein-coding RNA 2370 (LINC02370), an RNA gene that has a significant role in cancers. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the breast cancer scenario, IFNGR1 expression is abridged or wholly lost and the immunoreactivity of heterogeneous IFNGR1 is linked to the morphological heterogeneity in breast cancer cells . One of the essential biomarkers shortlisted in our study is long intergenic nonprotein-coding RNA 2370 (LINC02370), an RNA gene that has a significant role in cancers. , …”
Section: Resultsmentioning
confidence: 99%
“…50 One of the essential biomarkers shortlisted in our study is long intergenic nonprotein-coding RNA 2370 (LINC02370), an RNA gene that has a significant role in cancers. 51,52 To summarize, out of these nine drug-sensitive biomarkers, we consider TNFSF15, DCAF6, KDM6A, PHETA2, IFNGR1, and LINC02370 as potential biomarkers that are drugsensitive. These are further selected for their radiosensitivity or radioresistance.…”
Section: ■ Resultsmentioning
confidence: 99%
“…It has been shown that the downregulation of LHFPL3 expression was associated with reduced viability, proliferation, and invasiveness of human glioma cells ( Li et al, 2019 ). When the deletion occurs in LHFP3, its gene function is impaired, resulting in a worse prognosis for colorectal cancer patients ( Lin et al, 2021 ). KYAT1 and CR1 are protein-coding genes intersecting with the upregulated differential loci of HERV-K (HML-2) pol .…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that germline susceptibility and deletion structural variants can have an impact on the survival and therapeutic strategies for stage III colorectal cancer. For example, patients with germline DNA repair genetic variants and CEP72 deletion structural variants have better survival in CRCs [ 84 ]. Using AI model analysis, we could stratify the risk of cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%